A modern account of Iosipescu testing. (April 2018) - Stojcevski, Filip; Hilditch, Tim; Henderson, Luke C.
Abstract: The Iosipescu or V-notch shear test is a method capable of determining the shear modulus and interfacial shear strength (IFSS) of composites at the fiber-matrix interface. Although it has many advantages relating to its simplicity and the creation of pure shear stress region, it remains significantly underutilized for composite testing in comparison to single fiber fragmentation testing (SFFT) and short beam shear (SBS). Here an update is provided on the current status of Iosipescu testing which highlights developments and advances in modelling, fixture arrangement, testing, and several other remaining concerns relating to implementation.